2012
DOI: 10.14742/ajet.827
|View full text |Cite
|
Sign up to set email alerts
|

Developing technological pedagogical content knowledge in pre-service mathematics teachers through collaborative design

Abstract: Although many studies have shown the need to pay attention to teachers' preparation for the integration of technology in classroom practice, most teachers in Ghana have not had any preparation that develops their technological pedagogical content knowledge (TPCK).This paper presents a case study of four pre-service mathematics teachers from the University of Cape Coast, Ghana, who worked in two design teams to develop lessons, and subsequently taught in a technology-based environment for the first time. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
103
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 23 publications
(26 reference statements)
12
103
0
4
Order By: Relevance
“…The findings of the three studies conducted showed that the participants in the professional development program developed their technology-integration knowledge and skills as was revealed through self-reported data, lesson plans evaluation, interviews, focus group discussion and observations of the lessons in the classrooms. Studies by Agyei and Voogt (2012), Alayyar et al (2011) and Jimoyiannis (2010) also show that professional development programs that involve teachers in the collaborative design of technology-enhanced science or mathematics lessons are promising for teachers' development of technology integration knowledge and skills and lead to effects that are sustainable over time (cf. Agyei and Voogt 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the three studies conducted showed that the participants in the professional development program developed their technology-integration knowledge and skills as was revealed through self-reported data, lesson plans evaluation, interviews, focus group discussion and observations of the lessons in the classrooms. Studies by Agyei and Voogt (2012), Alayyar et al (2011) and Jimoyiannis (2010) also show that professional development programs that involve teachers in the collaborative design of technology-enhanced science or mathematics lessons are promising for teachers' development of technology integration knowledge and skills and lead to effects that are sustainable over time (cf. Agyei and Voogt 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One way of ensuring that prospective mathematics teachers develop instructional design capacities is to engage them in design activities as in creating instructional materials (Agyei & Voogt, 2012). Constructing instructional materials enables prospective teachers to think deeply about the kind of mathematical task and pedagogical approaches that affect students' learning processes.…”
Section: Web Pedagogiesmentioning
confidence: 99%
“…These moves are based on the supposition that when teachers teach with these technologies, students will develop substantial mathematical knowledge and lifelong learning skills (Buabeng-Andoh, 2012;MOESS, 2007). While the supposition holds a significant level of acceptance in literature (Guzeller & Akin, 2012;Beki & Guveli, 2008;Kong & Kwok, 2005), recent studies (Agyei & Voogt, 2012;Agyei & Voogt, 2011) have noted that most mathematics teachers have not had adequate preparation in terms of pedagogical knowledge, technical skills and readiness for such technology integration. It is thus imperative to question how teacher educators can prepare prospective teachers towards technology integration in Ghana.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations